LANGUAGE UTILIZATION AND COMMUNICATION BARRIERS IN SURABAYA'S CULTURAL HERITAGE:: INSIGHTS FROM LINGUISTIC LANDSCAPE ANALYSIS - Eka Dian Savitri; Kartika Nuswantara; Ratu, Aurelius; Hermanto (Linguistik Indonesia, 2024)
English This study applies linguistic landscape theory to analyze the language usage on cultural heritage information boards in Surabaya. It also explores the communication obstacles that impede tourists from accessing heritage sites. A total of 63 images were selected from a collection of 277 photographs using qualitative descriptive methodologies and photographic techniques. These images effectively depict various landscapes and cultural heritage places. The dataset classified media into categories such as road signs, name signboards, information boards, cultural heritage plaques, and establishment plaques. Indonesian is the dominant language, representing the country's sovereignty, but English is used for international tourists. The historical identity of Surabaya is represented by Dutch, Japanese, and Latin influences. Although the language environment is favorable, there are still difficulties in tourism communication due to insufficient information, unreadable text, and media that is not easily available at heritage sites. This study highlights the importance of enhancing signpost design to improve tourist experiences and effectively communicate heritage tourism by making use of language variety Indonesia Penelitian ini menerapkan teori lanskap linguistik untuk menganalisis penggunaan bahasa pada papan informasi warisan budaya di Surabaya. Laporan ini juga mengeksplorasi hambatan komunikasi yang menghalangi wisatawan mengakses situs warisan budaya. Sebanyak 63 gambar dipilih dari koleksi 277 foto dengan menggunakan metodologi deskriptif kualitatif dan teknik fotografi. Gambar-gambar ini secara efektif menggambarkan berbagai lanskap dan tempat warisan budaya. Kumpulan data tersebut mengklasifikasikan media ke dalam beberapa kategori seperti rambu jalan, papan nama, papan informasi, plakat warisan budaya, dan plakat pendirian. Bahasa Indonesia merupakan bahasa dominan yang mewakili kedaulatan negara, namun bahasa Inggris digunakan untuk wisatawan internasional. Identitas historis Surabaya diwakili oleh pengaruh Belanda, Jepang, dan Latin. Meskipun lingkungan bahasa mendukung, masih terdapat kesulitan dalam komunikasi pariwisata karena kurangnya informasi, teks yang tidak dapat dibaca, dan media yang tidak mudah didapat di situs warisan. Studi ini menyoroti pentingnya meningkatkan desain plang untuk meningkatkan pengalaman wisatawan dan mengkomunikasikan wisata warisan budaya secara efektif dengan memanfaatkan variasi bahasa